MAGIX, a new software for the analysis of complex gamma spectra. (January 2023) - Espagnon, I.; Allinei, P.G.; Simon, A.C.; Delarue, M.; Pontillon, Yves
Abstract: The MAGIX code (a French acronym standing for Automatic Gamma and X-ray Measurement) is a software developed to analyze γ/X spectra on the topic of severe accident diagnosis. Indeed, the gamma spectra obtained after a severe reactor core accident are complex because they are composed of hundreds of lines of short-lived fission products and Fukushima accident demonstrated a lack in robustness of data interpretation during a crisis. MAGIX allows a complete and entirely automatic analysis of the spectra, with identification of radionuclides and calculation of activities. It can analyze spectra measured by detectors with excellent resolution such as HPGe detectors as well as detectors with medium resolution (e.g. CZT and LaBr3 ). For most detectors, the analysis of the spectra can be done without a detection efficiency curve because its process can include the calculation of a relative detection efficiency. MAGIX accepts spectra corresponding to any experimental setup (energy slope, energy range, resolution, absorber, etc.). However, these experimental conditions can have an impact on the quality of the results. Results on spectra simulated in different configurations showed that the analysis of the HPGe spectrum with the user defined efficiency and with the MAGIX detection efficiency were close. Furthermore, they also showed that the accuracy of activities was similar with increasing energy slopes but decreased with resolution degradation, with fewer correctly identified radionuclides in this case. Highlights: MAGIX is an automatic software for identifying radionuclides and calculating their activities. It can analyze gamma spectra from HPGe, CZT and LaBr3 detectors. Several hundred lines can be analyzed simultaneously (i.e fission product spectra). Il doesn't need a user efficiency curve: it calculates a relative efficiency. Database filtering (JEFF3.3) is automatic and depends on the analysis stage.